Multidrug Resistance and Extensively Drug-Resistance in Staphylococcus aureus, Staphylococcus epidermidis, and Staphylococcus haemolyticus - Cliff Clarence Haliman; Dimas Seto Prasetyo; Conny R Tjampakasari; Fera Ibrahim; T Mirawati Sudiro (Microbiology Indonesia, 2022)
Antimicrobial resistance in bacteria has become a leading global public health issue. Staphylococcus sp. has an efficient mechanism to deal with antimicrobial agents that make them hard to treat in hospital-acquired and community-acquired infections. This study was conducted due to limited data about multidrug resistance and extensively drug resistance in Staphylococcus sp. in Indonesia. This study was a descriptive retrospective study using a cross-sectional design to get the prevalence and antimicrobial susceptibility of S. haemolyticus, S. aureus, and S. epidermidis. The data was secondary data extracted from WHONET 2022 software. This study’s data were from bacteria from samples sent to UKK LMK FKUI, Jakarta from 2017 to 2021 for routine diagnostic. In this study, we found that the prevalence of methicillin-resistant S.aureus was 24,9%, methicillin-resistant S.epidermidis was 65,5%, and methicillin-resistant S.haemolyticus was 86,8%. The prevalence of MDR S.aureus is less than S.epidermidis and S.haemolyticus, respectively. MDR S.haemolyticus was consistently above 85% each year, while S.epidermidis was above 50% and S.aureus was below 50%. XDR Staphylococcus was only found in S.aureus and S.haemolyticus, i.e. three and seven XDR isolates of S.aureus and S.haemolyticus respectively during 2017-2021. Although we could not find any pan-resistant isolates from all samples, we found methicillin-resistant S.aureus and S.haemolyticus isolates that were also resistant to vancomycin and linezolid. S.haemolyticus dan S. epidermidis were an important coagulase-negative Staphylococcus species that can’t be neglected due to the high percentage of MDR and the discoveries of XDR in S.haemolyticus so that they have the potential to disseminate resistance plasmids to the more virulent bacteria. Therefore we need to control the use of antimicrobial agent to prevent this resistance.